Cultivando Boas Práticas: a RDC-216/04 e a Cultura Organizacional na Perspectiva dos Gestores de Três Restaurantes Self-Services em Uberlândia-MG - Luciana Resende Ávila (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2010)
This research aims to reveal how the procedures established by the Anvisa resolution RDC-216/04 influence the organizational culture of self-services restaurants in Uberlandia, under their managers perspective. The research is qualitative and descriptive. The method applied was the comparative case study. The techniques used for data collecting were organizational document analysis, observation and semi-structured interviews. For the results analysis it was applied the techniques of content analysis and speech analysis under the triangulation perspective. The research findings showed homogeneities and heterogeneities in the interpretation of the managers on how that legislation brought influences to their organizational culture. Managers belonging to the same establishment diverged in their considerations about the relevance of certain procedures established by the resolution in the routine of their activities, although at the same time there were favorable and consistent interpretations among the interviewees, independent of belonging or not to the same organization.